Предмет: Алгебра,
автор: Аноним
Найдите значение выражения:
x(x+3)^2-(x-1)(x^2+x+1) при x-4
(P.S) ^ - степень.
Ответы
Автор ответа:
0
(x -1)(x² +x +1) =x^3 -1
x(x +3)² -(x^3 -1) =x(x² +6x +9) -x^3 +1 =x^3 +6x² +9x -x^3 +1 =6x² +9x +1 =6*4² +9*4 +1 =96 +36 +1 =133
x(x +3)² -(x^3 -1) =x(x² +6x +9) -x^3 +1 =x^3 +6x² +9x -x^3 +1 =6x² +9x +1 =6*4² +9*4 +1 =96 +36 +1 =133
Похожие вопросы
Предмет: Информатика,
автор: btrfyhfrvh
Предмет: Литература,
автор: rusakovap69
Предмет: Алгебра,
автор: Аноним
Предмет: Биология,
автор: mazichanh